Contemporary leadership in sport organizations - Scott, David 1956- (Champaign, IL Human Kinetics, 2014)
Contemporary Leadership in Sport Organizations blends research on leadership with practical application of the skills and knowledge that students will need on the job. This text provides sport management students with a comprehensive understanding of the complex topic of leadership in sport through a presentation of foundational and contemporary research, numerous practical examples and analytical exercises, and thought-provoking self-assessments and quotes. More than leadership tips from a sport personality, Contemporary Leadership in Sport Organizations translates classic and contemporary research in leadership into leadership skills and behaviors that are useful in present-day sport settings. Synopses of research findings are presented in table format for an accessible approach to understanding the three Rs of leadership: relationships, results, and responsibility. In addition, a variety of learning features reinforce content: Practical examples provide opportunities to critically consider the concepts under discussion; Chapter-opening objectives, as well as pre- and postchapter self-assessments, help students measure their understanding of chapter content; Specific examples and case studies applicable to a broad range of sport leadership roles put research into practice; On the Sidelines stories, Your Thoughts boxes, and questions at the end of chapters are incorporated throughout the book to provide examples and stimulate discussions applicable to a broad range of sport leadership roles across youth, amateur, intercollegiate, professional, and commercial sport organizations. Part I of the text offers a leadership primer, introducing the elements of business and educational environments in which sport organizations operate. Students will learn how leaders in sport organizations typically assume both managerial and leadership roles and how these roles integrate and diverge, and they will review the historical foundation and evolution of leadership theories from the academic literature. Part II covers applied leadership thought and action and how leaders can become more effective in addressing critical challenges of the present and future. Key topics such as decision making, organizational change, emotional intelligence, vision, strategic planning, and crisis management are discussed. Professional growth and development are the focus of part III, considering multiple approaches and tools for improving self-understanding, personal development, and leadership mentoring. Contemporary Leadership in Sport Organizations provides a foundational and contextualized body of information regarding thought and practice in leadership to inform and inspire students of sport management. Whether preparing for leadership roles in sport organizations or preparing for teaching, research, and academic study in the field of sport leadership, students will gain a solid understanding of the theoretical foundations of leadership in sport and how it is applied to sport-related organizations of all types and sizes.
Part I. A Leadership Primer -- Chapter 1. A Leadership Primer ; Defining Leadership ; Settings for Leadership in Sport Organizations ; Management and Leadership: Mutually Exclusive or Integrated? ; Levels of Analysis in Leadership ; Additional Frameworks for Understanding Leadership ; Historical Leadership Theory and Research ; Foundational Research in Sport Leadership ; Contemporary Leadership Thought: What We Have Learned ; Summary -- Chapter 2. Results, Relationships, and Responsibility ; Results ; Relationships ; Responsibility ; Summary -- Part II. Contemporary Thought in Leadership Applications for Sport Organizations -- Chapter 3. Emotional Intelligence and Leadership ; Defining Emotional Intelligence ; Why Is EI Important for Sport Leaders? ; Research and EI ; Applying EI in Organizational Leadership ; Summary -- Chapter 4. Building a Culture of Success ; Leadership and Organizational Culture: The Foundation ; Research in Sport Organizational Culture ; Building a Culture of Success in Sport Organizations ; Summary -- Chapter 5. Vision and Strategic Leadership ; Leadership and Vision in Sport Organizations ; Strategic Leadership ; Summary -- Chapter 6. Complexity and Problem Solving ; Changing Environment for Leadership ; Competencies and Skills for Creative Problem Solving ; Sources of Complex Problems in Sport Organizations ; Approaches to Problem Solving ; Summary -- Chapter 7. Change, Turnaround, and Crisis Leadership ; Change Leadership ; Turnaround Leadership ; Crisis Leadership ; Summary -- Chapter 8. Diversity Leadership ; Defining Diversity ; Perspectives on Gender, Culture and Nationality ; Surface-Level versus Deep-Level Diversity ; Diversity Representation and Embracing Diversity ; Diversity Representation in Sport ; Organizational Leadership and Diversity ; Women and Special Populations in Sport ; Leadership Competencies and Diversity ; Summary -- Chapter 9. Globalization and Leadership ; Terminology and Forms of Globalization ; Globalization in a Sport Context ; Globalization and Leadership ; Summary -- Part III. Developing Sport Leaders of the Future -- Chapter 10. Leadership Learning and Development ; Perspectives on Leadership Development ; How Do We Learn to Lead? ; Leadership Learning Applied ; Planning and Implementing Leadership Development ; Summary -- Chapter 11. Future Considerations ; Leadership Skills of the Future ; Sport Organizations as Learning Organizations ; Case Studies ; Final Thoughts.
Includes bibliographical references
Keywords: Leadership; Sports administration